A qualitative approach to assess operational barriers of service providers of community-based management of severe acute malnutrition program in a district of central India - Akanksha Tomar; Sunil Patel; Preeti Gupta; Rajesh Tiwari (Journal of Family Medicine and Primary Care, 2025)
Background: Though management of malnourishment in children has evolved, backed up by global evidence, community-based nutritional rehabilitation is a recent impetus to improve the outcomes, overcoming the challenges of facility-based rehabilitation. Yet operational hurdles of every initiative depend on local settings. Therefore, the aim of this study was to identify operational barriers in this technique, which will aid in strategy refinement for goal attainment and sustainability. Material and Methods: In this study, researcher assessed the operational barriers in the community-based management of severe acute malnutrition (CSAM) initiative through a qualitative approach using focus group discussions (FDGs) of service providers. Five focus groups discussions were conducted at the five sites with 43 participants. The groups were deliberately arranged to be profession-specific. All focus groups were conducted in Hindi lasted approximately 40-60 minutes and were comprised of 7–10 participants. Each focus group discussion was audio recorded and later transcribed and then independently reviewed by the team who identified six emerging themes. Results: The main operational barriers were regarding the knowledge about the CSAM initiative as all service providers knew about the launch of CSAM initiative but unaware of the criteria of enrolment in it and need of nutrition rehabilitation centers (NRCs) referral, administrative pressure to admit the children at NRC and overburden of service providers. Conclusion: Implementation of an effective public health approach for addressing SAM in India will require significant attention by policymakers to develop situation-specific, customized, and sustainable models of care.